FREKUENSI KUNJUNGAN POSYANDU DAN RIWAYAT KENAIKAN BERAT BADAN SEBAGAI FAKTOR RISIKO KEJADIAN STUNTING PADA ANAK USIA 3 – 5 TAHUN - Alﬁan Destiadi; Triska Susila Nindya; Sri Sumarmi (Media Gizi Indonesia, 2015)
Stunting is a chronic nutrition problem that requires precise intervention. Risk factors of stunting are need to be assessed to find the solution, such as attendance rate in integrated health post (posyandu) and weight gain. This was a case control study done in children aged 3-5 years old in Sidoarum village, Godean, Sleman, Yogyakarta. Sampling was done by simple random sampling technique with total 43 respondents in each group. Stunting is categorized based on the value of the z-score of height for age less than -2 SD. Primary data was obtained by interview, while attendance rate in integrated health post and weight gain were obtained through secondary data that is growth monitoring card (KMS) and monthly reports of integrated health post. Statistic test used for bivariate analysis was Chi-square and Multiple Logistic Regression for multivariate analysis. Result of bivariate analysis found that attendance rate in integrated health post and weight gain are related to stunting. Result showed that a low rate of attendance in integrated health post is the most dominant factor for the incidence of stunting in children aged 3-5 years (OR = 3.1, CI 95%= 1,268-7,623). This study concluded that children who are less active to come to integrated health post have 3.1 times higher risk of stunting compared to children who are actively come to integrated health postKeywords: attendance rate in integrated health post, children, stunting, weight gain